Prediction of efficiency in elite volleyball: multiple regression approach - Klaricic, I.; Grgantov, Z.; Jelaska, I. (Acta Kinesiologica, 2018)
The aim of this research was to identify the relationship between performance efficiency coefficients of the five phases of volleyball game (serve, reception, spike, block and dig) with a score difference, resulting in a win or a defeat in a set. According to the aim, a sample of 40 randomly selected sets played in the European League for Men in years 2011 and 2012 was used. Multiple linear regression analysis was applied on randomly selected half of the sample (N1=20) and cross-validated using the second half of the sample (N2=20). Due to significant validation statistics, it can be concluded that 78% of the difference in the set score can be explained by a system of predictor variables. It was determined that the spike and the dig have a significant relationship with the score difference in a set (p<0.05). The results implicitly point out dominance of attack compared to defense in elite volleyball. Additionally, they point out the importance of a spike as the game phase by which teams win the largest number of points in a volleyball set and also the importance of a dig by which teams prevent opponents in winning the points and making assumptions for winning points in the counter-attack.